The Impact of Prior Musculoskeletal Injury and Orthopaedic Surgery on Draft Position, Availability, and Performance in Major League Baseball: A Summative Analysis of 1, 890 Predraft Players. Issue 7 (29th July 2019) - Ramkumar, Prem N.; Navarro, Sergio M.; Luu, Bryan C.; Haeberle, Heather S.; Soloff, Lonnie; Frangiamore, Salvatore Joseph; Schickendantz, Mark S.
Objectives: Despite the value to future coaches, franchise management, and medical personnel, little is known about the epidemiology of musculoskeletal injuries and surgeries and their future impact prior to the MLB draft. The purpose of this study was to determine the (1) epidemiology of all musculoskeletal injuries and surgeries for predraft MLB players; (2) risk of injury or surgery on draft position; (3) risk of injury or surgery on availability within the first two years; and (4) risk of injury or surgery on performance. Methods: A total of 1, 890 medical records conducted by MLB team physicians prior to the draft were retrospectively reviewed from 2014 to 2018. Players were divided into three groups: non-injured (no musculoskeletal history), non-operative (previously injured but treated non-operatively), and operative (previous injury requiring surgery). Game statistics, including draft round, missed games, batting average (BA), and earned run average (ERA) for the first 2 seasons of MLB play were obtained for all available players, Players were matched for position, and confounders were analyzed for age, draft round using ANOVA analysis. Results: A total of 927 pitchers and 963 position players were evaluated, and 38.9% had no reported injury history, 48.6% reported injury but were treated non-operatively, and 12.4% were treated operatively. The most common pre-draft injuries were elbow tendonitis (n=312), UCL injury (n=212), and shoulder labral tear (n=76). The most common pre-draft treatments were physical therapy (922, 25.3%), UCL reconstruction (115, 3.2%), and fracture fixation (69, 1.9%). No difference was found between non-injured, non-operative, and operative groups in terms of draft position, games missed, and performance (BA for position players, p = 0.7246; ERA for pitchers, p=0.1956). After position matching, age and draft round were non-confounding. Conclusion: More than half of players entering the MLB report a musculoskeletal injury requiring treatment, with the most common pathology involves the shoulder and elbow. After position matching and analyzing for confounding factors like age and draft round, musculoskeletal history did not macroscopically impact draft position, short-term availability, or performance.